Adaptive current distribution method for parallel-connected PEMFC generation system considering performance consistency. (15th September 2019) - Wang, Tianhong; Li, Qi; Yang, Hanqing; Yin, Liangzhen; Wang, Xiaotong; Qiu, Yibin; Chen, Weirong
Highlights: An adaptive current distribution method is proposed in this paper. Performance, consistency and membrane area have been considered in this approach considered in this approach. A virtual droop control scheme is presented to improve bus voltage regulation. The proposed method could protect the underperforming stacks. Abstract: The proton exchange membrane fuel cell (PEMFC) stacks are not widely utilized in the sector of the transportation industry, due to their limited efficiency and durability. In order to apply FC stacks in high-power occasions, the FC stacks are usually connected in parallel to form a multi-stack FC system (MFCS). During the operation, since the current from the stacks changes dynamically with different operating parameters, they usually present different performance. In the MFCS, if the performance of one stack is unsatisfactory, operating the underperforming stack without corresponding protection measures may further degrade its performance and thus break down the system. In order to slow down the performance degradation of the FC stacks and keep the consistency of stacks' performance in MFCS, this paper has considered the effects of different stacks operating state and membrane area on the output current variations of stacks. And then an adaptive current distribution method realized by virtual droop technique considering the performance consistency of FC is proposed. Besides, this study builds a parallel-connected PEMFC generation system to verify the effectiveness of the proposed method. The validity of the proposed method has been demonstrated with experimental results. In addition, compared with the conventional control algorithm, the presented virtual droop control algorithm could get more satisfactory results. Such as improving the load voltage regulation and reducing the magnitude of the deviation between the actual output current and the reference current.